Within-reef biomass partitioning in a Mediterranean vermetid reef: a baseline for future monitoring - Mancuso, Francesco Paolo; Bisanti, Luca; Picone, Flavio; Chemello, Renato (Frontiers in Marine Science, 2025)
Biomass is an essential indicator for assessing the quality, stability, productivity, and health of ecosystems and it is increasingly used as a practical monitoring parameter within the Essential Ocean Variables (EOV) framework. In the Mediterranean Sea, vermetid reefs - unique bioconstructions structurally comparable to fringing coral reefs - play a significant role in coastal dynamics yet remain understudied. This study aimed to quantify the biomass distribution of the main structural species Dendropoma cristatum, seaweeds, and associated fauna found across three distinct reef zones: the inner edge (adjacent to the mainland with limited water movement), the cuvette (a central zone characterized by shallow, sheltered pools), and the outer edge (directly exposed to constant wave action). Rather than testing for a causal “zone effect”, we provide a site-specific quantitative baseline that can be used to track future change and to generate hypotheses on the environmental drivers of biomass patterns. Samples were collected from a vermetid reef in north-western Sicily, Italy, and biomass was estimated as ash-free dry weight (AFDW; a measure of organic matter excluding mineral content). This exploratory study of spatial patterns within one reef site revealed an average biomass of 321.4 g AFDW m−2, with values that increased from the inner edge to the outer zone within the single site studied. D. cristatum biomass was highest at the outer edge (likely reflecting its preference for stronger water movement and higher food supply), while seaweed biomass peaked in the outer edge and cuvette, where macroalgal diversity was greatest. Phytal fauna biomass was strongly correlated with seaweed biomass (R² = 0.68), emphasizing the role of macroalgae as ecosystem engineers, whereas vagile fauna were more abundant in the inner edge and cuvette, possibly benefiting from increased structural complexity and reduced predation. These site-specific findings illuminate spatial patterns of biomass distribution within this vermetid reef and provide essential baseline data for monitoring this location, whilst generating hypotheses for testing at other Mediterranean vermetid reef sites.